How successful has the National Football League been in extending its brand into the U.K. market since 2007? An investigation into the international brand extension of a major sports league. - Roston, Oliver (2014)
Since 2007, the National Football League has attempted to extend its brand into the U.K. market. Regular season fixtures having been played annual at London’s Wembley Stadium with increasing regularity, suggesting the organization has a long-term strategy to remain in the U.K. market. This despite the fact that the organization’s core product, American football, is associated predominantly with U.S. culture. This research project aimed to investigate whether the NFL’s brand extension into the U.K. market had achieved success, and add to the dearth of academic literature on the international brand extension of a major sports league. Extant literature was analysed prior to the main investigation of the study. It was important to contextualise brand literature, in particular brand extension literature, in order to discover that there was a marked gap in sports marketing literature regarding the international brand extension of a major sports league. A chapter on research methodology followed, where it was explained why qualitative research was selected, with the primary reason being that interviews would provide the study with great depth of information. Two sets of qualitative interviews were conducted with members of staff of NFL UK, the U.K. subsidiary of the organization, and a sample group of U.K. consumers. Findings were then extracted from the interviews and analysed thematically. It was discovered through the interviews that the strategy of extending its primary on field product over to the U.K. was crucial to the success of the extension, and this related to a previous study on product feature similarity. Furthermore, the role of free to air T.V. was seen as essential in distributing the extension product more widely, beyond the International Series- the primary on field extension product. Several consumers had an increased interest in the sport due to the extension, whilst almost all of the consumers engaged with the extension product in some way. The interviews also emphasised that the organisation needs to continue to work to improve the extension product, if it is to integrate itself further into the U.K. sports market and culture, with particular attention required for the off the field fan experience, and a lack of brand awareness in advertising. The research paper concluded that the NFL has achieved success in extending its brand into the U.K. market in the International Series games, consumer engagement and developing a strategy that other major sports leagues could look to. However, the organisation must work hard to continue to integrate the sport in the British sporting landscape, and focus on areas of weakness that came through in the consumer interviews. Following the conclusion, managerial implications were outlined for managers within the NFL with suggestions to improve advertising and fan experience based on interview responses. Managerial implications were also suggested for wider sports looking to extend their brand overseas, with the NFL a benchmark for success and strategy. However it was noted that not all strategies will suit all organisations. There were some limitations to the study, in particular the fact that only two interviews with NFL UK staff were possible, and the consumers were all based in London. Finally, future research around the topic was suggested, including investigating the role of free to air T.V. and the impact of the extension at grassroots level.